Honey antibacterial activity: A neglected aspect of honey quality assurance as functional food. (December 2021) - Majtan, Juraj; Bucekova, Marcela; Kafantaris, Ioannis; Szweda, Piotr; Hammer, Katherine; Mossialos, Dimitris
Abstract: Background: Honey is considered as a functional food with health-promoting properties. Its potent antibacterial and antibiofilm effects are the major attributes of so called 'medical-grade honey' which is topically used for the treatment of burns, wounds and skin disorders. Nevertheless, the current set of honey quality parameters adopted in the European Union do not include its biological properties. Furthermore, in light of the accelerated growth of scientific evidence, there is an urgent need to revise current qualitative tools, and to establish and certify more effective honey quality control. Scope and approach: This up-to-date narrative review aims to discuss the recent clinical evidence describing the use of honey in the management of various disorders including respiratory tract infections, metabolic and gastro-intestinal derangements. Current knowledge about the antibacterial activity of honey, as the most studied biological properties of natural honey, focusing on mechanism of action and the factors/compounds responsible for the antibacterial effects is also discussed. In addition, the weaknesses of current honey quality parameters are highlighted and a new potentially qualitative parameter that takes into account honey functionality is presented. Key findings and conclusions: Data from in vitro and in vivo experiments, as well as human clinical studies clearly indicate the importance and efficacy of honey as an antibacterial agent. Antibacterial activity can vary from honey to honey but must not be identical to the activity of the honey sugar content. In most cases, antibacterial activity can be negatively impacted by thermal processing and long-term storage and this activity is therefore a suitable and sensitive quality parameter. From a clinical point of view, we strongly advocate to solely use natural honey that has undergone only minimal processing in order to preserve the full spectrum of biological activities. Highlights: Honey is a functional food with health-promoting properties. Antibacterial activity is the most studied biological properties of honey. Weaknesses of current honey qualitative markers are discussed. New honey qualitative standard based on antibacterial activity is introduced.